Leitores como correspondentes: cartas de pequenos leitores à Ana Maria Machado - Kulesza, Bohdan Stanislaw (2010)
The present dissertation analyses the readers´letters sent to the author Ana Maria Machado, born in Rio de Janeiro in 1941. Most of her work is infant or young teenager books. The letters of this research discuss the children´s comments about her work. The letters are from 2004 to 2009, therefore showing their modern time. It is believed that, by studying this work, it is possible to analyse some reading practices at the Brazilian schools today, as well as the most reading book by young children: Bisa Bia, Bisa Bel. The work presented here is based on the formulation of Antonio Candido´s Literary System (1959) and a little influence of the Dialogism of Mikhail Bakhtin (1960), considering that the children experience two moments: as readers of Ana Maria Machado´s books and also authors of the letters sent to her.